Catalytic conversion of cellulose to C2–C3 glycols by dual association of a homogeneous metallic salt and a perovskite-supported platinum catalyst. Issue 14 (8th April 2016) - Girard, E.; Delcroix, D.; Cabiac, A.
Abstract : Dual combinations of homogeneous metallic salts and heterogeneous platinum catalysts were explored for the conversion of cellulose to C2 –C3 glycols. Abstract : A novel catalytic system based on the combination of a homogeneous metallic salt and a platinum catalyst supported on a zirconium-based oxide was explored for the selective conversion of cellulose to C2 –C3 glycols. Parameters such as the nature of the homogeneous catalyst, support effects and operating conditions were systematically varied to evaluate the potential of this dual catalytic system. Sharp analysis of reaction pathways led us to identify an optimal combination of cerium chloride and a barium zirconate-based platinum catalyst for the production of ethylene glycol and propylene glycol exhibiting substantial selectivities (>40%). The recyclability and the possible deactivation mechanisms of the catalytic system were ultimately investigated.